The effects of star grading on the management of the South African hotel and tourist industry and its future - Muller, P. R. J.(Peter Rudolf Jacques) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.B. & A.) -- University of Stellenbosch, 1969.